Use of Mobile Health on Adherence among HIV Positives Person: A Literature Review - Anung Widi Armunanto; Rr. Tutik Sri Hariyati; Agung Waluyo (STIKep PPNI Jawa Barat, 2023)
Aim: Antiretroviral is the main key to improving the quality of life and among ways to prevent the transmission of diseases due to HIV. In the use of drugs in the long term, psychosocial problems that arise often become barriers to patient adherence. This paper aims to show various forms of application and see the benefits derived from the use of mobile health (m-Health) in increasing the adherence of HIV positive patients. Method: The method used is a review of journals from Pubmed published no more than the last five years about the use of mobile health in those infected with HIV. Result: The result is that all existing articles provide explanations about the application of mobile health and positive result in supporting adherence, but there is a note regarding the consideration of its implementation goals and the services provided as well as the retention rate after using after several time. Conclusion: The conclusion is that mobile health provides benefits to increase adherence and help overcome the patient’s psychosocial problems.